Desainer Grafis yang Menciptakan dan Menjual Produk Berupa Barang - Hastjarjo Boedi Wibowo (Bina Nusantara University, 2013)
Graphic designers in their economic activities are more widely known simply as seller of the product in the form of services. Whereas in reality it is not so since the days of Art and Craft movement spearheaded by William Morris at the end of the 19th century. William Morris, a graphic designer, had created products with good design for sale. Many reasons are behind it, starting from desires to break free from pressures of the clients, expanding spaces to express creativity to economic motives. Discussion of graphic designers crossing border of disciplines by creating products is very interesting. They do not just perform the profession on the basis of orders (client-based), but they are able to read the market that will absorb the products they created. Even, they create market trend (as a trendsetter). At this level, a designer does not just make value-added work, but already at the level of creating new value (value creation).